Wild things! : acts of mischief in children's literature - Bird, Betsy; Danielson, Julie; Sieruta, Peter D. (Candlewick Press, 2014)
Did Laura Ingalls cross paths with a band of mass murderers? Why was a Garth Williams bunny tale dubbed "integrationist propaganda"? For adults who are curious about children's books and their creators, here are the little-known stories behind the stories. A treasure trove of information for a student, librarian, new parent, or anyone wondering about the post-Harry Potter book biz, Wild Things! draws on the combined knowledge and research of three respected and popular librarian-bloggers. Told in affectionate and lively prose, with numerous never-before-collected anecdotes, this book chronicles some of the feuds and fights, errors and secret messages found in children's books and brings contemporary illumination to the warm-and-fuzzy bunny world we think we know. Secret lives, scandalous turns, and some very funny surprises -- these essays by leading kids' lit bloggers take us behind the scenes of many much-loved children's books.